Children's art museum collections as Linked Open Data. (10th August 2021) - Kotis, Konstantinos; Angelis, Sotiris; Chondrogianni, Maria; Marini, Efstathia
It has been recently argued that it is rather beneficial to cultural institutions to provide their datasets as Linked Open Data, to achieve cross-referencing, interlinking, and integration with other datasets in the LOD cloud. In this paper, we present the Greek Children's Art Museum (GCAM) linked dataset, along with dataset and vocabulary statistics, as well as lessons learned from the process of transforming the collections to HTML-embedded structured data using the Europeana Data Model and the Schema.org model. The dataset consists of three cultural collections of 121 child artworks (paintings), including detailed descriptions and interlinks to external datasets. In addition to the presentation of GCAM data and the lessons learned from the experimentation of non-ICT experts with LOD paradigm, the paper introduces a new metric for measuring datasets quality in terms of links to and from other datasets.